44.2.6.11 Applications of Allenes in Organic Synthesis (Update 2022) - Tius,M. A. (Knowledge Updates 2022/1, 2022)
This chapter is an update to the earlier Science of Synthesis article (Section 44.2.6) that described the applications of allenes in organic synthesis. An attempt has been made to cover the literature from the end of 2005 through to approximately the end of June 2020. Allenes generally participate in the same reactions as alkenes, but their strain and the presence of the sp-hybridized carbon atom enable additional pathways. Advances in transition-metal-mediated asymmetric catalysis, especially involving gold and rhodium, have led to the development of many of the novel highly enantioselective processes that are discussed.
Keywords: Reference Work; Science of Synthesis; allenes; allenic compounds; asymmetric catalysis; coupling reactions; cyclobutanes; gold complexes; Pauson–Khand reaction; Nazarov cyclization; rhodium catalysts